2006
DOI: 10.1002/jid.1344
|View full text |Cite
|
Sign up to set email alerts
|

Assessing interventions to improve child nutrition: a theory‐based impact evaluation of the Bangladesh Integrated Nutrition Project

Abstract: The Community-Based Nutrition Component of the Bangladesh Integrated Nutrition Project sought to improve nutritional status through nutritional counselling and supplementary feeding for malnourished children and pregnant women. This paper presents a theory-based impact evaluation of this programme. Both counselling and feeding suffered from problems of inappropriate targeting strategies and a failure to reach intended groups. While counselling has changed women's knowledge it has had less of an impact on behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 10 publications
(2 reference statements)
1
49
0
Order By: Relevance
“…A similar result was found by an assessment of the Bangladesh Integrated Nutrition Project (PINB) which also showed that the project had no significant impact on wasting in children 22 . However, our results differ from those found by an assessment of the Bolsa Familia program in Brazil which found that the intervention led to an improvement in nutritional status among participating children 23 .…”
Section: Variablesupporting
confidence: 75%
“…A similar result was found by an assessment of the Bangladesh Integrated Nutrition Project (PINB) which also showed that the project had no significant impact on wasting in children 22 . However, our results differ from those found by an assessment of the Bolsa Familia program in Brazil which found that the intervention led to an improvement in nutritional status among participating children 23 .…”
Section: Variablesupporting
confidence: 75%
“…65 In Bangladesh, the program of supplementary feeding with nutrition education was based on the premise that 'bad' habits' and poor nutritional knowledge were responsible for child undernutrition. 75 Thus, in this study as in others, 75 caregivers were given nutritional counseling. In some studies where supplementation had limited impact, levels of health and nutritional literacy in the local community were extremely low, hence programmes began from a low base and sometimes had to counter prevailing folk myths and 'lay epidemiology'.…”
Section: Agentic Mechanisms In Caregiver (General)mentioning
confidence: 76%
“…43 Authors of the Bangladesh study attributed poor results, in part, to the fact that they hadn't reached out to other members of the family (father, mother-inlaw) who made nutritional decisions. 75 Third, the caregiver must be open to the suggestion that an undernourished child may need to be treated differently and 'favoured' over other children in the family. This is difficult to achieve.…”
Section: Agentic Mechanisms In Caregiver (General)mentioning
confidence: 99%
“…For example, a study conducted in Bangladesh attributed poor results in part to engaging with the mother only, instead of also engaging with other members of the family who made decisions about nutrition. 87 Some communities may have strong social norms about nutrition and infant feeding that compete with the instructions from the programme. For example, for a supplementary feeding programme to be successful, a caregiver needs to believe and act on the idea that an undernourished child may need to be treated differently and 'favoured' over other children in the family.…”
Section: Constraining Factors Enabling Factorsmentioning
confidence: 99%